Handbook of tyranny - Deutinger, Theo, 1971-; McGetrick, Brendan (Zürich : Lars Müller Publishers, 2018)
'Handbook of Tyranny' portrays the routine cruelties of the twenty-first century through a series of detailed non-fictional graphic illustrations. None of these cruelties represent extraordinary violence. They reflect day-to-day implementation of laws and regulations around the globe. Every page of the book questions our current world of walls and fences, police tactics and prison cells, crowd control and refugee camps. The dry and factual style of storytelling through technical drawings is the graphic equivalent to bureaucratic rigidity born of laws and regulations. The level of detail depicted in the illustrations of the book mirror the repressive efforts taken by authorities around the globe.
The tragedy of territory -- Free entry -- Walls & fences -- Bunker buster -- Terrorist groups -- Refugee camps -- Total demolition -- Defensive city -- Crowd control -- Prison cells -- A vast conspiracy -- Death penalty -- Slaughterhouse -- Green fortress.
boek
Keywords: Deutinger, Theo, -- 1971-.; Violence -- Pictorial works; History, Modern -- 21st century; Terrorism -- Pictorial works; Prisons -- Pictorial works; Refugee camps